Pengaruh Penggunaan Media Audio Visual Oleh Guru Pendidikan Agama Kristen dan Budi Pekerti Terhadap Keaktifan Belajar: Peserta Didik Kelas IX di SMPN 4 Siborongborong Tahun Pembelajaran 2024/2025 - Tio Narly Harahap; Tianggur Medi Napitupulu; Regina BM Nainggolan; Dorlan Naibaho; Boho Parulian Pardede (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this study was to determine the positive and significant influence of the Use of Audio Visual Media by Christian Religious Education and Character Education Teachers on the Learning Activity of Grade IX Students at SMPN 4 Siborongborong in the 2024/2025 Academic Year. The method used in this study is a quantitative research method with descriptive inferential data analysis. The population was all grade IX students of SMP Negeri 4 Siborongborong totaling 206 people and a sample of 34 people was determined using the Purposive sampling technique. Data were collected using a positive closed questionnaire of 32 items. The results of the data analysis show that there is a positive and significant influence of the Use of Audio Visual Media by Christian Religious Education and Character Education Teachers on the Learning Activity of Class IX Students at SMPN 4 Siborongborong in the 2024/2025 Academic Year as evidenced by the following data analysis: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.851> rtable ( = 0.05, n = 34) = 0.339. b) Significant relationship test obtained tcount value = 9.167> ttable ( = 0.05, dk = n-2 = 32) = 2.036. 2) Influence test: a) Regression equation test, obtained regression equation Ŷ = 10.02 + 0.80X. b) Regression determination coefficient test (r2) = 72.4%. 3) Hypothesis testing using the F test obtained Fcount > Ftable, namely 84.334 > 1.79. Thus Ha is accepted and H0 is rejected.